Peapod Assemblies of Au and Au/Pt Nanoparticles Encapsulated within Hollow Silica Nanotubes. Issue 8 (14th March 2017) - Byoun, Wongyun; Yoo, Hyojong
Abstract: Nanoparticle assemblies within hollow nanoshells represent versatile structures which enable efficient nanosystems with colligative properties of nanoparticles for a variety of applications. In this report, we present a simple and high yielding solution‐based synthetic strategy for peapod‐shaped Au nanoparticle assembly encapsulated within hollow silica nanotubes ( pp multi‐Au@SiO2 NTs). One‐dimensional, [multiple Au nanodot] core–[silica] shell nanowires (multi‐Au@SiO2 NWs) are preferentially synthesized based on reverse microemulsion (water‐in‐oil) techniques. By thermal treatment of multi‐Au@SiO2 NWs in aqueous polyvinylpyrrolidone (PVP) solution, pp multi‐Au@SiO2 NTs can be successfully fabricated. Further growth of Pt on the Au nanoparticles in pp multi‐Au@SiO2 NTs can lead to the generation of [Au] core‐[Pt] shell (Au/Pt) nanoparticle assembly surrounded by silica nanotubes ( pp multi‐Au/Pt@SiO2 NTs). Abstract : Through the thermal treatment of multi‐Au@SiO2 NWs in aqueous PVP solution, peapod‐like Au nanoparticle assembly encapsulated within hollow silica nanotubes ( pp multi‐Au@SiO2 NTs) are fabricated. Pt growth on the Au NPs in pp multi‐Au@SiO2 NTs leads to the generation of [Au] core‐[Pt] shell nanoparticle assembly surrounded by silica nanotubes ( pp multi‐Au/Pt@SiO2 NTs).